Association between posttraumatic stress disorder (PTSD) severity and ego structure of the Nanai people - Yoko Ota; Natalia Korshunova; Masashi Demura; Midori Katsuyama; Hironobu Katsuyama; Sri Ratna Rahayu; Kiyofumi Saijoh (Environmental Health and Preventive Medicine, 2017)
Abstract Background A man-made chemical disaster occurred in the Amur River, leading to posttraumatic stress disorder (PTSD) in the Nanai people indigenous to the river’s surrounding area. PTSD severity measured by the total scores of Impact of Event Scale-Revised (IES-R) (Total-I) and Clinician-Administered PTSD Scale (CAPS) (Total-C) were not always identical in terms of demographic and ethnocultural characters. It is possible that the results derived using the Total-I and Total-C may differ for persons with different backgrounds and/or individual characteristics. In this study, the associations between PTSD severity and personal characteristics were evaluated. Methods The study was a field-type survey including 187 randomly selected participants (75 males and 112 females). In addition to Total-I/Total-C, scores for each IES-R/CAPS item, Intrusion, Avoidance, and Hyperarousal, and Ego Structure Test by Ammon (ISTA) score were examined to evaluate their personal characteristics. Results No specific trends in ISTA score were obvious among four groups defined according to Total-I/Total-C. The results of principal component analysis showed that all IES-R/CAPS items contributed positively to the 1st axis but to the 2nd axis in a different manner. ISTA items did not always show correlations to each other, but principal component analysis suggested that Construct contributed positively and Destruct and Deficient (with the exception of Destruct sexuality) contributed negatively. High IES-R scores were associated with Construct Aggression and Deficient Inner demarcation, but high CAPS score was less likely to exhibit Construct Narcissism. Conclusion To avoid the misdiagnosis of PTSD, usage of both IES-R/CAPS may be required. Simultaneous application of personality/ego tests may be helpful, but appropriate numbers of their questions would be important.